2015
DOI: 10.3390/ijerph120504739
|View full text |Cite
|
Sign up to set email alerts
|

Antimony, Arsenic and Chromium Speciation Studies in Biała Przemsza River (Upper Silesia, Poland) Water by HPLC-ICP-MS

Abstract: In this paper the total concentration of As, Cr, Sb, pH and the red-ox potential of water and sediment samples of the Biała Przemsza River were determined. The arsenic (AB, MMA, DMA, As(III), As(V)), chromium (Cr(III), Cr(VI)) and antimony (Sb(III), Sb(V)) forms were studied by HPLC-ICP-MS. Ions were successfully separated on Hamilton PRP-X100: (AB, MMA, DMA, As(III), As(V)), Dionex Ion Pac AS-7 (Sb(III), Sb(V)) and Dionex IonPac AG7 columns: Cr(III), Cr(VI) with LOD 0.16 μg/L, 0.08 μg/L, 0.09 μg/L, 0.012 μg/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…A slightly higher one was observed at BP1 in Chrząstowice (about 100 μg/L). It increased until December 2014, when it reached 326 μg/L at BP5 (Sosnowiec) (Jabłońska-Czapla 2015 ). Due to the total Mn content in the Biała Przemsza River water, it can be classified within classes II and below II of the surface water quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A slightly higher one was observed at BP1 in Chrząstowice (about 100 μg/L). It increased until December 2014, when it reached 326 μg/L at BP5 (Sosnowiec) (Jabłońska-Czapla 2015 ). Due to the total Mn content in the Biała Przemsza River water, it can be classified within classes II and below II of the surface water quality.…”
Section: Resultsmentioning
confidence: 99%
“…The sequential chemical extraction also demonstrated that arsenic and chromium were bound to the oxide and sulfide and organic matter fractions in the Biała Przemsza River bottom sediments. At BP1, arsenic was mainly bound to oxides in all seasons (Jabłońska-Czapla 2015 ). For antimony, there were seasonal changes in the ion exchange fraction percentage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NOM bound Sb was determined by calculating the difference between total and free Sb. The detailed procedure can be found elsewhere [30]. The elemental compositions of the studied HA, SA, and L-cysteine were determined using an elemental analyzer (Vario EL III, Elementar, Langenselbold, Hesse, Germany).…”
Section: Methodsmentioning
confidence: 99%